Winter lovers: engajamento e participação no universo de game of thrones da internet - Santos, Natália de Oliveira (2016)
The formation of groups acquired new features with the arrival of the internet. The links before straitened between family, work groups and close friends today reach long distances through online communities. These communities represent groups that have affinities and common interests, and use the community space to discuss these. Examples of these communities are those related to franchise Game of Thrones, a literary phenomenon that has expanded by various media, including the social, television, and communities. This report aims to present the work steps and the theoretical reflection, necessary for the achievement of a final product in file format, which aimed to measure the engagement and participation of GOT fans on the Internet, especially in two Facebook GOT communities during the fifth season of the series aired on HBO.